Melampaui Mimbar: Transformasi Dakwah dalam Lanskap Media Kontemporer - Lasmana, Galih; Galih (Penerbit Cahaya Kata, 2025)
This article examines the paradigm shift in da'wah (Islamic preaching) from conventional pulpit-based methods to strategic adaptations within the contemporary media landscape. Developments in information and communication technology have created new spaces for the dissemination of religious messages, requiring preachers to innovate in their approaches, formats, and audience reach. Using qualitative literature research methods, this study analyzes various digital media platforms—from social media and video platforms to podcasts—as modern da'wah media. The results show that this transformation involves not only technical changes in delivery but also a restructuring of narratives, interactions, and the formation of virtual communities. Challenges such as disinformation, polarization, and limitations in digital ethics are also discussed. This article concludes that adapting da'wah to contemporary media is not merely an option but a necessity to maintain the relevance and effectiveness of religious messages in the digital age.